Rigid units revisited. Issue 5 (5th September 2018) - Phillips, Anthony E.
Abstract : Rigid‐unit modes, which allow coordination polyhedra to remain undistorted and hence cost little energy, provide a way of understanding many important physical properties. Campbell et al. [ Acta Cryst. (2018). A74, 408–424] have developed an elegant new algebraic approach to finding these distortion modes. Abstract : Rigid‐unit modes, which allow coordination polyhedra to remain undistorted and hence cost little energy, provide a way of understanding many important physical properties. Campbell et al. [ Acta Cryst. (2018). A74, 408–424] have developed an elegant new algebraic approach to finding these distortion modes.